Carbon fiber structure electrode interface performance sample preparation and test method
By performing surface modification and droplet debonding test on carbon fiber structure electrodes, the problem of difficult and poor reproducibility of sample preparation and poor reproducibility of the interface bonding performance test of carbon fiber structure electrodes in the prior art is solved, and high efficiency is achieved. Accurate interface performance testing.
Patent Information
- Application Number
- CN202411575838.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively test the interface bonding performance of carbon fiber structure electrodes, especially in the preparation and testing of single fiber extraction specimens, there are problems such as difficulty in sample preparation and poor repeatability.
Surface modified carbon fibers are used as electrode fibers, and micro-droplet debonding tests are carried out on the tensile tester, combined with observations from ultra-deep field microscopes, interfacial performance samples of carbon fiber structure electrodes are prepared and tested. This method does not require a dedicated composite interface evaluation equipment, and through the modification of the horizontal tensile tester, it realizes cost-effective interface testing.
Through this method, the interface strength of the carbon fiber structure electrode can be obtained more accurately, and the interface debonding process can be observed dynamically, and the carbon fiber electrode structure design can be guided, improving the efficiency and accuracy of interface performance testing.
Smart Images

Figure CN119491412A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of structural energy storage composite material testing, and specifically relates to a method for preparing and testing a sample of a carbon fiber structure electrode interface performance. Background Art
[0002] For the electrochemical performance of structural batteries, the electrode interface is the site where lithium ions must undergo necessary electrochemical reactions. At the electrode interface, the ionic liquid needs to be in contact with the carbon fiber surfactant, which means that both the electrolyte solid phase and the liquid phase need to be in physical contact with the fiber surface. Due to the limited fiber / matrix adhesive surface area, the interfacial bonding performance is expected to be lower than that of the traditional fiber / matrix interface. For this very complex interface region, further research is needed to understand the interfacial bonding performance between the structural electrolyte and the carbon fiber electrode.
[0003] The interfacial performance of carbon fiber structure electrodes can be characterized by interfacial bonding strength tests, which include micro-debonding tests, single fiber pull-out tests, and single fiber fragmentation tests. These test results can accurately represent the interfacial shear strength (IFSS) of the composite material.
[0004] When preparing a single fiber pull-out specimen, a single fiber is vertically embedded in the resin matrix, and the length of the embedded fiber is controlled, requiring that the fiber does not break when it is pulled out of the matrix. During the pull-out experiment, the resin block is fixed, and force is applied to the outer end of the single fiber until the fiber is completely pulled out of the matrix. The force is transmitted from the fiber to the matrix through the interface. Single fiber pull-out has a wide range of applications and can be applied to various reinforcing fiber / matrix combination systems. The limitation of the single fiber pull-out experiment lies in the preparation of the specimen: different single fibers have different critical lengths when embedded in different resins. If the length is too long, the single fiber will easily break before debonding occurs at the interface, which increases the difficulty of sample preparation and the repeatability of the experiment is poor.
[0005] The droplet adhesion test is an improved version of the single fiber pullout test, which solves the problem that thin fibers are easy to break during the test. At the same time, the droplet debonding test also has the advantages of simple sample preparation, multiple droplets on a single fiber, multiple tests, and high efficiency of interface performance testing. The external load acts directly on the fiber end and is transferred to the matrix through the interface. The bottom or top of the matrix is fixed in a symmetrical loading manner, such as Figure 1 As shown in FIG. 1 , a single fiber / resin droplet sample is placed in a slit formed by two fixed blades. When the single fiber is stretched, the blades fix the droplet on the fiber and record the force-displacement curve of the fiber being pulled out of the droplet. When the shear force reaches a critical value, debonding occurs at the interface and the maximum load F is recorded. Combined with the length L of the droplet-coated fiber and the fiber diameter d, the interface shear strength is obtained using formula (1).
[0006] τ=F / πdL (1)
[0007] By proposing a method for preparing and testing the microdroplet debonding interface performance specimens of carbon fiber structure electrodes, a basis is provided for the interface performance evaluation of carbon fiber structure electrodes, which is of great significance for the performance optimization research of supporting structure energy storage composite materials. Since the microdroplet debonding test requires the use of specific experimental equipment (such as HM410 interface shear strength evaluation device, Toei Co., Ltd., Japan), such equipment is quite expensive due to its high precision. This method is based on a horizontal tensile tester and has been modified. Compared with the above equipment, it is simpler and cheaper, and the test accuracy is guaranteed.
[0008] The ultra-depth-of-field microscope can observe characteristic structures such as the modified layer on the fiber surface. The ultra-depth-of-field microscope is used to photograph and monitor the debonding process of electrode fiber droplets. The changes in the surface morphology of the electrode fiber during the interface debonding process can be dynamically observed, and the influence of the modified layer on the fiber / resin interface can be observed, so as to provide guidance for the design of the modified layer of the carbon fiber structure electrode. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing and testing a sample of the interface performance of a carbon fiber structure electrode.
[0010] Based on the above purpose, the present invention adopts the following technical solutions:
[0011] A method for preparing a carbon fiber structure electrode interface performance sample, the process is as follows:
[0012] (1) Using surface-modified carbon fiber as a carbon fiber electrode, the electrode fiber monofilament is peeled off from the carbon fiber electrode under a magnifying glass;
[0013] (2) fixing the two ends of the electrode fiber monofilament to the two sides of the concave-shaped carrier respectively, so that the middle part of the electrode fiber monofilament is suspended in the middle of the concave-shaped carrier and is in a stretched state;
[0014] (3) mixing the resin, pore-forming agent, and curing agent and stirring them evenly to obtain a structured electrode resin solution;
[0015] (4) Use a syringe to dip the structured electrode resin solution and drop it on the electrode fiber monofilament. Drop multiple droplets on one fiber and solidify it to obtain an electrode fiber monofilament test sample containing multiple resin droplets.
[0016] Preferably, in step (1), the surface-modified carbon fiber is a carbon fiber modified by a carbon active substance or a silicon active substance, including carbon nanotubes and silicon particles.
[0017] Preferably, the resin is 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane resin, the pore-forming agent is polyethylene glycol 200, the curing agent is PACM curing agent, the mass ratio of resin, pore-forming agent and curing agent is 1:(2-3):(0.2-0.6), and the curing process is: first keep warm at 120-150°C for 50min-70min, and then keep warm at 160-200°C for 20min-40min.
[0018] Preferably, the length of a single droplet-coated fiber is 70-240 μm.
[0019] The above-mentioned sample is used to test the interface performance of the carbon fiber structure electrode, and the process is as follows:
[0020] (1) Fix the concave-shaped carrier with the test sample on the test bench of the tensile testing machine, clamp the two ends of the fiber in the fixture of the tensile testing machine, drag the electrode fiber with tension at a certain loading rate, so that the droplets on the fiber contact with the fixed tool, use the ultra-depth of field microscope to take pictures of the continuous changes in the microscopic surface morphology of the electrode fiber, and record the maximum load displayed by the tensile testing machine during the test and the force-displacement curve during the loading process. When the tension rapidly decays by more than 30%, the test is terminated;
[0021] (2) Calculate the shear strength of the carbon fiber structure electrode interface using formula (1);
[0022] τ=F / πdL (1) (3) The force-displacement curve of the sample is used in combination with the ultra-depth-of-field microscopic images corresponding to each point on the curve to obtain the corresponding electrode fiber interface debonding results, thereby studying the microscopic change behavior of the electrode modified layer during the interface debonding process.
[0023] Preferably, the loading rate in step (1) is 0.01-0.1 mm / min.
[0024] Since the test results are somewhat discrete, this experiment requires multiple tests to obtain a more accurate average interface shear strength.
[0025] The present invention tests the interface performance of the carbon fiber structure electrode based on a tensile testing machine and an ultra-depth of field microscope, can more accurately obtain the interface strength of the carbon fiber structure electrode, and can obtain the change law of the microscopic morphology of the carbon fiber electrode surface during the interface destruction process of the carbon fiber structure electrode, which is of great significance for guiding the design of the carbon fiber electrode structure.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. No special composite material interface evaluation equipment is required. This test can be performed using a tensile testing machine;
[0028] 2. Through the ultra-depth-of-field microscope, the interface debonding process of the carbon fiber electrode monofilament during the test can be observed more clearly. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments:
[0030] Figure 1 It is a schematic diagram of a microdroplet debonding test in the prior art;
[0031] Figure 2 This is the electron microscope image of the sputtered Si modified fiber surface;
[0032] Figure 3 This is the electron microscope image of the CNT modified fiber surface;
[0033] Figure 4 This is a schematic diagram of the droplet debonding sample carrier and test;
[0034] Figure 5 This is the sample image under the ultra-depth-of-field microscope;
[0035] Figure 6 This is the SEM image of CNT modified fiber after debonding;
[0036] Figure 7 Force-displacement curve for the droplet test. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific examples, but it should not be understood as a limitation of this patent.
[0038] Embodiment 1:
[0039] A method for testing the interface performance of a carbon fiber structure electrode, the process is as follows:
[0040] (1) Carbon nanotube (CNT) surface-modified carbon fibers and Si surface-modified carbon fibers were used as carbon fiber electrodes.
[0041] Preparation of Si-modified carbon fiber droplet debonding samples: The silicon layer was sputtered on the surface of the carbon fiber fabric by magnetron sputtering technology, and the thickness of the Si layer was 0.1-1 μm. The SEM photos of the obtained samples are shown in Figure 2 As shown by Figure 2 It can be seen that a relatively uniform Si modified layer is formed on the surface of carbon fiber through magnetron sputtering.
[0042] Preparation of CNT modified carbon fiber droplet debonding sample: CNT is grown on the surface of carbon fiber fabric by CVD method, and the thickness of CNT layer is 0.5-2.5μm. SEM photos of CNT modified carbon fiber droplet debonding samples are shown in Figure 3 As shown by Figure 3 It can be seen that uniform CNTs are grown on the surface of carbon fibers.
[0043] (2) 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane resin and polyethylene glycol 200 were added to a beaker in a ratio of 1:3 and stirred. After stirring evenly, a curing agent PACM in an amount of 0.6 times the mass of the resin was added and stirred for 15 minutes to obtain a structured electrode resin solution.
[0044] (3) Under a magnifying glass, peel off the electrode fiber monofilament from the carbon fiber electrode to ensure that the peeled electrode fiber is a single fiber; fix the two ends of the electrode fiber monofilament on the two sides of the concave-shaped carrier, such as Figure 4 As shown, the electrode fiber is suspended in the middle and is in a stretched state.
[0045] (4) Using a syringe, drip the prepared structured electrode resin solution onto the electrode fiber monofilament, drip multiple droplets onto one fiber, and ensure that the sizes of the droplets are as close as possible to reduce the discreteness of the experimental results. After curing, multiple droplets with a fiber embedded length of 70-120 μm are obtained; the curing refers to first curing at 130° C. for 1 hour, then curing at 180° C. for 0.5 hour, and cooling to room temperature.
[0046] (5) The concave-shaped carrier with the test sample is fixed on the test bench of the tensile testing machine. The microdroplet on the electrode fiber is dragged to contact the fixed tool with a tensile force at a loading rate of 0.1 mm / min. The tool is 5 μm away from the fiber surface. The continuous change of the microscopic surface morphology of the electrode fiber is captured using an ultra-depth of field microscope, such as Figure 5 As shown, the maximum load displayed by the tensile testing machine during the test and the force-displacement curve during the loading process are recorded at the same time. When the tensile force rapidly decays by more than 30%, the test is terminated. Figure 5 It can be seen that the resin droplets completely cover the modified part of the carbon fiber, and the data tested on the surface is the interface shear strength between the modified fiber and the electrode resin.
[0047] (6) The shear strength of the carbon fiber structure electrode interface is calculated using formula (1); Figure 7 The force-displacement curve of the sample in the experiment is analyzed by combining the ultra-depth-of-field micrographs corresponding to each point on the curve to obtain the corresponding electrode fiber interface debonding results. Figure 7 It can be seen that when the force applied to one end of the fiber reaches its maximum value and begins to decay, the surface resin is completely debonded from the fiber.
[0048] (7) Pass Figure 6 SEM observations showed that there was still resin residue on the debonded surfaces of both modified carbon fibers, indicating that the modified layer did improve the interface properties of the carbon fiber electrode.
[0049] Carbon fiber electrode interface shear strength test value
[0050]
[0051] Embodiment 2:
[0052] A method for testing the interface performance of a carbon fiber structure electrode, the process is as follows:
[0053] (1) The carbon nanotube (CNT) surface-modified carbon fiber and the Si surface-modified carbon fiber of Example 1 were used as carbon fiber electrodes.
[0054] (2) 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane resin and polyethylene glycol 200 were added to a beaker in a ratio of 1:3 and stirred. After stirring evenly, a curing agent PACM in an amount of 0.6 times the mass of the resin was added and stirred for 15 minutes to obtain a structured electrode resin solution.
[0055] (3) Under a magnifying glass, peel off the electrode fiber monofilament from the carbon fiber electrode to ensure that the peeled electrode fiber is a single fiber; fix the two ends of the electrode fiber monofilament on the two sides of the concave-shaped carrier, such as Figure 4 As shown, the electrode fiber is suspended in the middle and is in a stretched state.
[0056] (4) Using a syringe, drip the prepared structured electrode resin solution onto the electrode fiber monofilament, drip multiple droplets onto one fiber, and ensure that the sizes of the droplets are as close as possible, so that after curing, multiple droplets with a fiber embedded length of 120-170 μm are obtained; the curing refers to first curing at 130° C. for 1 hour, then curing at 180° C. for 0.5 hour, and cooling to room temperature.
[0057] (5) The concave-shaped carrier with the test sample is fixed on the test bench of the tensile testing machine, and the microdroplet on the electrode fiber is dragged to contact the fixed tool with a tensile force at a loading rate of 0.1 mm / min, and the tool is 5 μm away from the fiber surface. The continuous change of the microscopic surface morphology of the electrode fiber is photographed using an ultra-depth of field microscope, and the force-displacement curve during the loading process is recorded at the same time. When the tensile force rapidly decays by more than 30%, the test is terminated.
[0058] (6) Record the maximum load during the test and calculate the shear strength of the carbon fiber structure electrode interface using formula (1); obtain the force-displacement curve of the sample, and analyze it in combination with the ultra-depth of field microscopy images corresponding to each point on the curve to obtain the corresponding electrode fiber interface debonding results.
[0059] (7) Through SEM observation, it was found that there was still resin residue on the debonded surface of the two modified carbon fibers, indicating that the modified layer did improve the interfacial performance of the carbon fiber electrode.
[0060] Carbon fiber electrode interface shear strength test value
[0061]
[0062] Embodiment 3:
[0063] A method for testing the interface performance of a carbon fiber structure electrode, the process is as follows:
[0064] (1) The carbon nanotube (CNT) surface-modified carbon fiber and the Si surface-modified carbon fiber of Example 1 were used as carbon fiber electrodes.
[0065] (2) 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane resin and polyethylene glycol 200 were added to a beaker in a ratio of 1:3 and stirred. After stirring evenly, a curing agent PACM in an amount of 0.6 times the mass of the resin was added and stirred for 15 minutes to obtain a structured electrode resin solution.
[0066] (3) Under a magnifying glass, peel off the electrode fiber monofilament from the carbon fiber electrode to ensure that the peeled electrode fiber is a single fiber; fix the two ends of the electrode fiber monofilament on the two sides of the concave-shaped carrier, such as Figure 4 As shown, the electrode fiber is suspended in the middle and is in a stretched state.
[0067] (4) Using a syringe, drip the prepared structured electrode resin solution onto the electrode fiber monofilament, drip multiple droplets onto one fiber, and ensure that the sizes of the droplets are as close as possible, so that after curing, droplets with a length of 180-240 μm embedded in multiple fibers are obtained; the curing refers to first curing at 130° C. for 1 hour, then curing at 180° C. for 0.5 hour, and cooling to room temperature.
[0068] (5) The concave-shaped carrier with the test sample is fixed on the test bench of the tensile testing machine, and the microdroplet on the electrode fiber is dragged to contact the fixed tool with a tensile force at a loading rate of 0.1 mm / min, and the tool is 5 μm away from the fiber surface. The continuous change of the microscopic surface morphology of the electrode fiber is photographed using an ultra-depth of field microscope, and the force-displacement curve during the loading process is recorded at the same time. When the tensile force rapidly decays by more than 30%, the test is terminated.
[0069] (6) Record the maximum load during the test and calculate the shear strength of the carbon fiber structure electrode interface using formula (1); obtain the force-displacement curve of the sample, and analyze it in combination with the ultra-depth of field microscopy images corresponding to each point on the curve to obtain the corresponding electrode fiber interface debonding results.
[0070] (7) Through SEM observation, it was found that there was still resin residue on the debonded surface of the two modified carbon fibers, but the fibers were mostly broken during the test, indicating that the resin droplets were too large and easily caused the fibers to break during the test, thereby increasing the discreteness of the test.
[0071] Carbon fiber electrode interface shear strength test value
[0072]
[0073] Embodiment 4:
[0074] A method for testing the interface performance of a carbon fiber structure electrode, the process is as follows:
[0075] (1) The carbon nanotube (CNT) surface-modified carbon fiber and the Si surface-modified carbon fiber of Example 1 were used as carbon fiber electrodes.
[0076] (2) Add 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane resin and polyethylene glycol 200 in a ratio of 1:3 into a beaker and stir. After stirring evenly, add 0.6 times the mass of the resin as curing agent PACM and stir for 15 minutes to obtain a structured electrode resin solution. (3) Peel the electrode fiber monofilament from the carbon fiber electrode under a magnifying glass to ensure that the peeled electrode fiber is a single fiber; fix the two ends of the electrode fiber monofilament on the two sides of the concave carrier, such as Figure 4 As shown, the electrode fiber is suspended in the middle and is in a stretched state.
[0077] (4) Using a syringe, drip the prepared structured electrode resin solution onto the electrode fiber monofilament, drip multiple droplets onto one fiber, and ensure that the sizes of the droplets are as close as possible, so that after curing, multiple droplets with a fiber embedded length of 120-170 μm are obtained; the curing refers to first curing at 130° C. for 1 hour, then curing at 180° C. for 0.5 hour, and cooling to room temperature.
[0078] (5) The concave-shaped carrier with the test sample is fixed on the test bench of the tensile testing machine, and the microdroplet on the electrode fiber is dragged to contact the fixed tool with a tensile force at a loading rate of 0.01 mm / min, and the tool is 5 μm away from the fiber surface. The continuous change of the microscopic surface morphology of the electrode fiber is photographed using an ultra-depth of field microscope, and the force-displacement curve during the loading process is recorded at the same time. When the tensile force rapidly decays by more than 30%, the test is terminated.
[0079] (6) Record the maximum load during the test and calculate the shear strength of the carbon fiber structure electrode interface using formula (1); obtain the force-displacement curve of the sample, and analyze it in combination with the ultra-depth of field microscopy images corresponding to each point on the curve to obtain the corresponding electrode fiber interface debonding results.
[0080] Carbon fiber electrode interface shear strength test value
[0081]
[0082] Embodiment 5:
[0083] A method for testing the interface performance of a carbon fiber structure electrode, the process is as follows:
[0084] (1) The carbon nanotube (CNT) surface-modified carbon fiber and the Si surface-modified carbon fiber of Example 1 were used as carbon fiber electrodes.
[0085] (2) 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane resin and polyethylene glycol 200 were added to a beaker in a ratio of 1:3 and stirred. After stirring evenly, a curing agent PACM in an amount of 0.6 times the mass of the resin was added and stirred for 15 minutes to obtain a structured electrode resin solution.
[0086] (3) Under a magnifying glass, peel off the electrode fiber monofilament from the carbon fiber electrode to ensure that the peeled electrode fiber is a single fiber; fix the two ends of the electrode fiber monofilament on the two sides of the concave-shaped carrier, such as Figure 4 As shown, the electrode fiber is suspended in the middle and is in a stretched state.
[0087] (4) Using a syringe, drip the prepared structured electrode resin solution onto the electrode fiber monofilament, drip multiple droplets onto one fiber, and ensure that the sizes of the droplets are as close as possible, so that after curing, multiple droplets with a fiber embedded length of 120-170 μm are obtained; the curing refers to first curing at 130° C. for 1 hour, then curing at 180° C. for 0.5 hour, and cooling to room temperature.
[0088] (5) The concave-shaped carrier with the test sample is fixed on the test bench of the tensile testing machine, and the microdroplet on the electrode fiber is dragged to contact the fixed tool with a tensile force at a loading rate of 0.1 mm / min, and the tool is 10 μm away from the fiber surface. The continuous change of the microscopic surface morphology of the electrode fiber is photographed using an ultra-depth of field microscope, and the force-displacement curve during the loading process is recorded until the test is terminated.
[0089] (6) Record the maximum load during the test, and use formula (1) to calculate the shear strength of the carbon fiber structure electrode interface; obtain the force-displacement curve of the sample, and analyze it in combination with the ultra-depth of field micrographs corresponding to each point on the curve to obtain the corresponding electrode fiber interface debonding results. In this example, some of the resin microspheres broke from the middle, and a large number of them were not peeled off, resulting in an increase in the experimental discreteness.
[0090] Carbon fiber electrode interface shear strength test value
[0091]
[0092] The following table shows the measured values of the interfacial shear strength of the droplet debonding of each embodiment.
[0093]
[0094] Comparing the above embodiments, the lengths of the resin droplet-embedded fibers tested in Examples 1-3 are 70-120 μm, 120-170 μm, and 180-240 μm, respectively. According to the comparison of Cv values, the test data obtained when the resin droplet length is between 120-170 μm is more stable; Example 2 and Example 4 are comparisons of loading rates, which are 0.1 mm / min and 0.01 mm / min, respectively. The Cv values of the obtained results are not much different. In order to improve the test efficiency and reduce the requirements for the loading accuracy of the instrument, the loading rate can be set to 0.1 mm / min; the distances from the tool to the fiber in Example 2 and Example 5 are 5 μm and 10 μm, respectively. The data obtained from the test are more accurate when the distance from the tool to the fiber is 5 μm, and there are more unpeeled parts of some resin microspheres in Example 5, so a distance from the tool to the fiber of 5 μm is selected.
[0095] The above description is only a partial implementation mode of the present invention. For ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the principle of the present invention. These improvements and substitutions should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a carbon fiber structure electrode interface performance sample, characterized in that: The process is as follows: (1) Using surface-modified carbon fiber as a carbon fiber electrode, the electrode fiber monofilament is peeled off from the carbon fiber electrode under a magnifying glass; (2) Fixing the two ends of the electrode fiber monofilament on the two sides of the concave-shaped carrier respectively, so that the middle part of the electrode fiber monofilament is suspended in the middle of the concave-shaped carrier and is in a stretched state; (3) Mixing the resin, pore-forming agent, and curing agent and stirring them evenly to obtain a structured electrode resin solution; (4) Use a syringe to dip the structured electrode resin solution and drop it on the electrode fiber monofilament. Drop multiple droplets on one fiber and solidify it to obtain an electrode fiber monofilament test sample containing multiple resin droplets.
2. The method for preparing a carbon fiber structure electrode interface performance sample according to claim 1, characterized in that: In step (1), the surface-modified carbon fiber is a carbon fiber modified by a carbon active substance or a silicon active substance.
3. The method for preparing a carbon fiber structure electrode interface performance sample according to claim 1, characterized in that: In step (4), the resin is 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane resin, the pore-forming agent is polyethylene glycol 200, the curing agent is PACM curing agent, and the mass ratio of the resin, the pore-forming agent, and the curing agent is 1:(2-3):(0.2-0.6).
4. The method for preparing a carbon fiber structure electrode interface performance sample according to claim 1, characterized in that: The curing process is: first keep warm at 120~150℃ for 50min~70min, then keep warm at 160~200℃ for 20min~40min.
5. The method for preparing a carbon fiber structure electrode interface performance sample according to claim 1, characterized in that: The lengths of all individual droplet-coated fibers were 70-240 μm.
6. A carbon fiber structure electrode interface performance sample prepared by the preparation method according to any one of claims 1 to 5.
7. A method for testing the interface performance of a carbon fiber structure electrode using the sample according to claim 6, characterized in that: The process is as follows: (1) Fix the concave-shaped carrier with the test sample on the test bench of the tensile testing machine, clamp the two ends of the fiber in the fixture of the tensile testing machine, drag the electrode fiber with tension at a certain loading rate, so that the droplets on the fiber contact the fixed tool, use the ultra-depth of field microscope to take pictures of the continuous changes in the microscopic surface morphology of the electrode fiber, and record the maximum load displayed by the tensile testing machine during the test and the force-displacement curve during the loading process. When the tension rapidly decays by more than 30%, the test is terminated; (2) Calculate the shear strength of the carbon fiber structure electrode interface using formula (1); F is the maximum load, L is the droplet length, d is the fiber diameter, and τ is the interfacial shear strength; (3) The force-displacement curve of the sample is analyzed in combination with the ultra-depth-of-field microscopic images corresponding to each point on the curve to obtain the corresponding electrode fiber interface debonding results, thereby studying the microscopic change behavior of the electrode modified layer during the interface debonding process.
8. The testing method according to claim 7, characterized in that: The loading rate in step (1) is 0.01~0.1mm / min.
Citation Information
Patent Citations
Interfacial property test method of carbon nano-tube surface modified fiber
CN109596464A
Preparation method of micro-debonding sample of heterogeneous cured resin system
CN110655334A
Method for testing interfacial shear strength of connecting rod composite material
CN110967296A
Test piece for evaluating interfacial adhesiveness, molding method thereof and testing method for evaluating interfacial adhesiveness of reinforcing fiber and resin
JP2006003244A
Unidirectional reinforcement fabric and method for manufacturing the same, and prepreg and carbon fiber composite material using the same
JP2012246583A